PROBLEMS OF MORALITY IN THE WORK OF KYRGYZ SINGER IMPROVISERS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
This article discusses the problems of morality in the work of Kyrgyz singer improvisersof the XIXearly XX centuries, in the works of which the positive and negative aspects of human behavior are widely highlighted.The views of Kyrgyz singer improviserson such concepts of morality as «good»,»evil», «justice», «injustice», «happiness», «patriotism», «public good», «duty», «honor», «friendship», «work», etc. are revealed in detail.
Keywords: morality, work, good, justice, society, person, poet, morality, idea, opinion.